Diskursus Fenomenologi Agama Dalam Studi Agama-Agama - Rahman, Ryan Arief; Bin Cecep Mustopa, Rodhi Hakiki; Fikri, Muhammad Dhiaul; Kusuma, Amir Reza; Rohman, Abdul (AL-ADYAN, 2021)
The imbalance in the study of religions not only occurs in the history of its development but also its methodology. Starting from the Western scientists who are not objective in describing comprehensively the development of this discipline that sets aside the contribution of Muslim scientists in it. Which gives an effect on the paradigm that produces a methodology that is very westernized. This knowledge cannot be separated from the role of contemporary Muslim scientists and researchers, by using the method of critical analysis, the author tries to Islamize one of the main methods in the study of religions namely the phenomenology of religion. The goal is to be friendly and can be used by Muslim scientists and researchers. By the concept and method of Islamization of Syed Muhammad Naquib Al-Attas's on science (de-westernization, integration and Islamization), the authors formulated three problematic aspects in the phenomenology of religion, those are paradigms, epoche method and neutral. After the process of criticism as a form of de-westernization, the author then integrates with the research methods of Muslim scientists. Thus, the phenomenology of religion was successfully Islamized and friendly for Muslim researchers to be used.  Ketimpangan dalam studi agama-agama tidak hanya terjadi dalam sejarah perkembangannya tetapi juga metodologinya. Berawal dari para ilmuwan Barat yang tidak objektif dalam memaparkan perkembangan disiplin ilmu ini secara komprehensif yang menyisihkan kontribusi para ilmuwan muslim di dalamnya. Hal demikian berpengaruh terhadap paradigma yang menghasilkan metodologi yang sangat berbau kebarat-baratan. Disiplin ilmu ini tidak bisa lepas dari peran ilmuwan dan peneliti muslim kontemporer, dengan menggunakan metode analisis kritis, penulis mencoba untuk mengislamisasikan salah satu metode utama dalam studi agama-agama yakni fenomenologi agama. Tujuannya agar ramah dan dapat digunakan oleh para ilmuwan dan peneliti muslim. Dengan konsep dan metode islamisasi ilmu pengetahuan Syed Muhammad Naquib Al-Attas (dewesternisasi, integrasi dan islamisasi), penulis merumuskan tiga aspek yang bermasalah dalam fenomenologi agama yaitu paradigma, metode epoche dan netral. Setelah proses kritik sebagai bentuk dewesternisasi, kemudian penulis mengintegrasikan dengan metode penelitian ilmuwan muslim. Oleh yang demikian, fenomenologi agama berhasil diislamisasikan dan ramah untuk digunakan para peneliti muslim.